1988
DOI: 10.2307/1941256
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Limitation of Production and Decomposition in Prairie, Mountain Meadow, and Pine Forest

Abstract: The responses of decomposition and primary production to nitrogen supply were investigated in a shortgrass prairie, a mountain meadow, and a lodgepole pine forest. Nitrogen (N) supply was increased by applying ammonium nitrate, or decreased by applying sucrose. The litterbag technique was used to follow decomposition ofleaves of the dominant plants: blue grama (Bouteloua gracilis) from the prairie, western wheatgrass (Agropyron smithii) from the meadow, and lodgepole pine (Pinus contorta) from the forest.Soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
212
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(240 citation statements)
references
References 24 publications
24
212
1
3
Order By: Relevance
“…1), suggesting "home-field advantage" (Gholz et al, 2000;Hunt et al, 1988). Our study design further demonstrates this "homefield advantage" phenomenon (Gholz et al, 2000;Hunt et al, 1988) for the first time through the generation of experimental resource histories. These gains in function are consistent with the expected properties of microbial communities -fast growth rates, physiological flexibility and rapid evolutionthat enable them to respond rapidly to new conditions (Allison and Martiny, 2008).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…1), suggesting "home-field advantage" (Gholz et al, 2000;Hunt et al, 1988). Our study design further demonstrates this "homefield advantage" phenomenon (Gholz et al, 2000;Hunt et al, 1988) for the first time through the generation of experimental resource histories. These gains in function are consistent with the expected properties of microbial communities -fast growth rates, physiological flexibility and rapid evolutionthat enable them to respond rapidly to new conditions (Allison and Martiny, 2008).…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, the soil inoculum sourced from the hardwood environment (inoculum B) had the greatest initial litter mineralization ( Fig. 1), suggesting "home-field advantage" (Gholz et al, 2000;Hunt et al, 1988). Our study design further demonstrates this "homefield advantage" phenomenon (Gholz et al, 2000;Hunt et al, 1988) for the first time through the generation of experimental resource histories.…”
Section: Discussionmentioning
confidence: 56%
“…Evidence from some reciprocal leaf decomposition experiments have shown faster decomposition in leaf litter placed in the community of origin rather than in another plant community, suggesting that some detrital communities may be adapted to breaking down particular types of substrata. This pattern is referred as 'home-court advantage', and has been found for low-quality leaf litter in forest plantations in Brazil (De Asiss Olivereira et al, 1998) and for some temperate pine and aspen forests (Hunt et al, 1998;González et al, 2003). In our study, microfungal decomposers showed faster decomposition of their own substratum or substrata that were related or similar to their source leaves as compared to unrelated and dissimilar substrata.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast, soil bacterial and archaeal communities remained statistically indistinguishable among treatments after 5 years and through most of the 2-year sampling period that followed (Figure 2a). Research has shown that many characteristics of a plant assemblage-composition (Hunt et al, 1988;Bardgett et al, 1999;Smalla et al, 2001;Wieland et al, 2001;Nunan et al, 2003;Ayres et al, 2006), diversity (Gruter et al, 2006) and production (Zak et al, 2003)-can affect the microbial composition of underlying soils. Any snapshot measurement in our experiment might have affirmed this idea for our grassland system as well, but analyzing across seasons we find a soil community characterized by marked seasonal dynamics and longer-term decoupling from aboveground change.…”
Section: Discussionmentioning
confidence: 99%